Digital Public Participation and Responsive Governance in Village Development Planning - I Wayan Astawa; Gede Wirata; Sri Sulandari (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study examines how digital public participation supports village development planning as a manifestation of responsive regional autonomy in the 2025 era. Village development in Indonesia increasingly emphasizes participatory governance, but citizen involvement is often limited due to elite dominance, low digital literacy, and unequal access. The purpose of this study is to analyze the mechanisms of digital participation, supporting factors, challenges, and their implications for regional autonomy. The method used is a qualitative literature study through analysis of academic publications, policy documents, and related empirical findings. The results show that digital participation occurs in various forms, ranging from information disclosure, online consultations, interactive feedback tools, to co-creation mechanisms, but its implementation varies across villages. Factors such as infrastructure, digital literacy, leadership, and institutional integration influence the effectiveness of participation, while key challenges include the digital divide, weak platform maintenance, and minimal integration with formal planning. In conclusion, digital participation can strengthen autonomy if supported by strong governance, a hybrid model, and consistent feedback mechanisms.